The effect of strike action on the value and volatility of the South African Rand - Gordon, Ross Patrick (Rhodes University, Faculty of Commerce, Department of Economics, 2015)
This study analyses whether the advent of strike action has an effect on the value and volatility of the South African Rand compared with the US Dollar. The literature suggests that strike action can have a significant effect on the exchange rate in terms of either value or volatility, and consequences can result that cause inefficiencies in the economy; inhibiting employment and economic growth. Strike action has become common place in South Africa, with 2012 alone recording 99 strikes, 45 of which were "wildcat" or unprotected strikes. This study uses GARCH and Intervention Analyses to determine what the resulting effects of the strikes might be on the exchange rate. The analysis used ZAR/USD exchange rate data for the period January 2000 to October 2013, and covered 72 of the most significant strikes in terms of lost man-days. The results are mixed, suggesting that the effects of strikes do not always conform to expectations (increased volatility and a depreciation in the Rand), and that outside factors affecting the global economy may have a more significant effect on the exchange rate than strikes on their own.
Keywords: Foreign exchange rates -- South Africa; Strikes and lockouts -- South Africa -- Economic aspects; South Africa -- Foreign economic relations; South Africa -- Economic conditions -- 1991-; Rand, -- South African; Dollar, American